A PIGH mutation leading to GPI deficiency is associated with developmental delay and autism. Issue 6 (26th April 2018) - Nguyen, Thi Tuyet Mai; Mahida, Sonal; Smith‐Hicks, Constance; Campeau, Philippe M.
Abstract: We identified an individual with a homozygous missense variant (p.Ser103Pro) in a conserved residue of the glycosylphosphatidylinositol (GPI) biosynthesis gene PIGH . This gene encodes an essential component of the phosphatidylinositol N‐acetylglucosaminyltransferase complex, in the first step of the biosynthesis of GPI, a glycolipid anchor added to more than one hundred human proteins, several being critical for embryogenesis and neurological functions. The affected individual had hypotonia, moderate developmental delay, and autism. Unlike other reported individuals with GPI deficiency, the proband did not have epilepsy; however, he did have two episodes of febrile seizures. He had normal alkaline phosphatase and no brachytelephalangy. Upon analysis of the surface expression of GPI‐anchored proteins on granulocytes, he was demonstrated to have GPI deficiency. This suggests that PIGH mutations may cause a syndrome with developmental delay and autism, but without an epileptic encephalopathy, and should increase the awareness of the potentially deleterious nature of biallelic variants in this gene. Abstract : An individual with a homozygous missense variant (p.Ser103Pro) in PIGH had hypotonia, moderate developmental delay, and autism. This gene is key for the biosynthesis of the glycosylphosphatidylinositol (GPI) anchor added to several neuronal proteins. Upon analysis of the surface expression of GPI‐anchored proteins on granulocytes, he was demonstrated to have GPI deficiency. This suggest that PIGH mutations may cause a syndrome with developmental delay and autism, but without epilepsy.